Controlled manipulation of CNTs in glass/epoxy composites with cut-outs using non-uniform electric field. (4th May 2021) - Pothnis, Jayaram R.; Kalyanasundaram, Dinesh; Gururaja, Suhasini
Abstract : In this work, an effective methodology to incorporate aligned carbon nanotubes (CNTs) in long fiber composites in the presence of geometric discontinuities has been studied. Unidirectional (UD) glass/CNT-epoxy composites containing circular cut-outs were used as representative of a common discontinuity. Multi-walled (MW) CNTs were introduced in the composites via the epoxy matrix and aligned using low-frequency non-uniform AC electric field. This work discusses the methodology to control CNT alignment around the cut-out with the objective of enhancing the stiffness locally. The effectiveness of CNT alignment was assessed indirectly through the mapping of electrical resistance and polarized Raman spectroscopy. A strong correlation was found between the targeted CNT alignment state and the measured resistance values around the cut-out. As a precursor to developing glass/CNT-epoxy hierarchical composites, the response of MW-CNTs in the epoxy resin system was assessed at various input voltage levels in correlation with the weight fraction (wt.%) of CNTs. While a change in electrical resistance by ~3 orders of magnitude was found along the direction of CNT alignment in the hierarchical composites, a change in electrical resistance by ~5 orders of magnitude was observed in the CNT-epoxy composites in comparison with that of the respective control samples.